Embodiment and the new shape of black theological thought - Pinn, Anthony B. (Religion, race, and ethnicity., 2010)
"Anthony Pinn is one of the grand philosophers wrestling with the problem of evil. This masterful and magisterial book confirms his deserved reputation--Cornel West, Princeton University.